2016
DOI: 10.1016/j.jssc.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

LiBi3S5—A lithium bismuth sulfide with strong cation disorder

Abstract: Terms of Use AbstractAmong chalcogenide semiconductors for thermoelectric applications, alkali-metal bismuth compounds occur in many complex compositions favorable for high performance. Although LiBi 3 S 5 had been announced in 1977, the potential 1D lithium-ion conductor has hitherto eluded selective synthesis and structure determination. In this study, we present a solid-state route to phase-pure LiBi 3 S 5 powder starting from LiBiS 2 and Bi 2 S 3 . Neutron diffractograms and lithium-NMR spectra reveal its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…From the atomic scale point of view the elementary hopping processes have to be characterized in many cases by 3D diffusion unless diffusion of the ions is preferred along a special direction of the crystal structure. Apart from such anisotropic movements in materials offering 3D diffusion there are layer-structured and channel-structured ion conductors with significantly constraint migration pathways [30,65,[79][80][81][82][83][84]. Lithium transition metal dichalcogenides represent a typical class of materials that offer 2D diffusion in their van-der-Waals gaps [83].…”
Section: Ion Diffusion In Layer-structured (Nanocrystalline) LI X mentioning
confidence: 99%
“…From the atomic scale point of view the elementary hopping processes have to be characterized in many cases by 3D diffusion unless diffusion of the ions is preferred along a special direction of the crystal structure. Apart from such anisotropic movements in materials offering 3D diffusion there are layer-structured and channel-structured ion conductors with significantly constraint migration pathways [30,65,[79][80][81][82][83][84]. Lithium transition metal dichalcogenides represent a typical class of materials that offer 2D diffusion in their van-der-Waals gaps [83].…”
Section: Ion Diffusion In Layer-structured (Nanocrystalline) LI X mentioning
confidence: 99%
“…From a structural point of view we can explain this finding because of cation disorder. Our structural analyses [34] has shown that immobile Bi 3+ ions may easily block the Li diffusion pathways, thus hindering ion migration along the channels of the sulfide. In such a case, Li ion diffusion is expected to be largely mediated by defects in the various sub-lattices enabling the ions to diffuse via non-regular lattice sites.…”
Section: Libi 3 Smentioning
confidence: 97%
“…LiBi 3 S 5 also crystallizes with a channel-like structure and the Li ions residing inside the channels have, thus, access to a spatially rather restricted diffusion pathway (see Figure 11b). We followed a solid-state route to prepare phasepure gray-black LiBi 3 S 5 powder starting from LiBiS 2 and Bi 2 S 3 [34]. Neutron diffractograms and lithium NMR spectra reveal its crystal structure to be a cation-disordered variety of the AgBi 3 S 5 type (synthetic pavonite; monoclinic, C2/m).…”
Section: Libi 3 Smentioning
confidence: 99%
See 1 more Smart Citation
“…With LiBi 3 S 5 (monoclinic, C2/m), we were able to selectively synthesize and characterize an announced, but hitherto elusive compound [65]. The material had been deemed a potentially fast one-dimensional lithium-ion conductor; to our dismay, NMR studies showed it to be moderate at best.…”
Section: Strongly Disordered: Libi 3 Smentioning
confidence: 99%